Synthesis and DFT Study of the Complexation of Schiff Base Derived Curcumin and L-Tyrosine with Al(III), Ag(I), and Pb(II) Metal Ions - Ali Mahmood Ali; Tagreed Hashim Al-Noor; Eid Abdalrazaq; Abdel Aziz Qasem Jbarah (Universitas Gadjah Mada, 2021)
The multi-dentate Schiff base ligand (H2L), where H2L=2,2'-(((1,3,5,6)-1-(3-((l1-oxidaneyl)-l5-methyl)-4-hydroxyphenyl)-7-(4-hydroxy-3-methoxyphenyl)hepta-1,6-diene-3,5-diylidene)bis(azaneylylidene))bis(3-(4-hydroxyphenyl)propanoic acid), has been prepared from curcumin and L- Tyrosine amino acid. The synthesized Schiff base ligand (H2L) and the second ligand 1,10-phenanthroline (phen) are used to prepare the new complexes [Al(L)(phen)]Cl, K[Ag(L)(phen)] and [Pb(L)(phen)]. The synthesized compounds are characterized by magnetic susceptibility measurements, micro elemental analysis (C.H.N), mass spectrometry, molar conductance, FT-infrared, UV-visible, atomic absorption (AA), 13C-NMR, and 1H-NMR spectral studies. The characterization of the synthesized complexes shows that the environment surrounding the central metal ion in the complexes adopted a distorted octahedral configuration. Moreover, the conductivity measurements show a non-electrolytic character for the [Pb(L)(phen)] complex and an electrolytic character for the [Al(L)(phen)]Cl and K[Ag(L)(phen)] complexes. The experimental infrared data are supported by density functional theory (DFT) calculations using the B3LYP level of theory and LANL2DZ basis set. The vibrational frequencies of the molecules are computed using the optimized geometry obtained from the DFT calculations. The calculated vibrational frequencies have been compared with obtained experimental values. 1H and 13C-NMR chemical shifts were computed for the H2L ligand using the DFT/GIAO method. Additionally, the molecular electronic structures of the complexes have been investigated by DFT calculations.